Rancangan Mini Ekosistem bagi Budi Daya Ikan Nila (Oreochromis niloticus) dan Tanaman Genjer (Limnocharis flava) di dalam Ember yang Dilengkapi dengan Sistem Peringatan Amonia - Natalia Eka Prasetia; Ramadhani Eka Putra; Sparisoma Viridi (Institut Pertanian Bogor, 2022)
Environmental conditions and fish stocking density in tilapia cultivation (Oreochromis niloticus) are important factors in determining the success of the cultivation process and supporting optimal fish growth. This study used four treatments, namely A, B, C, and D, for 3, 5, 7, and 9 fish, respectively. The purpose of this study was to determine the effect of raccoon tail plants (Ceratophyllum demersum) and genjer plants (Limnocharis flava) on tilapia mortality, determine the ratio of feed conversion and the effect on ammonia concentrations, determine the effect of ammonia concentrations on the productivity of genjer plants, determine the warning system modeling on ammonia concentrations, as well as calculate mass and energy balance in the cultivation system of tilapia and genjer. The result is that the planting of raccoon tails and genjer in the system significantly affects tilapia mortality. The average value of feed conversion ratio from treatments A, B, C, and D were 1.75; 1.36; 3.51; and 2.87, respectively. The effect is significant and directly proportional to ammonia concentration and genjer productivity. The ammonia warning system modeling is in the form of linear equations, namely y = 0.2085x - 0.0193 with R2 = 0.9692. This system's balance of mass and energy can be divided into three subsystems, namely, fish acclimatization, fish cultivation, and genjer cultivation. Keywords: ammonia, genjer, modelling, tilapia